Endothelin‐1 contributes to endothelial dysfunction and enhanced vasoconstriction through augmented superoxide production in penile arteries from insulin‐resistant obese rats: role of ETA and ETB receptors. (December 2014) - Sánchez, A; Martínez, P; Muñoz, M; Benedito, S; García‐Sacristán, A; Hernández, M; Prieto, D
<x xml:space="preserve">Abstract</x> Background and Purpose We assessed whether endothelin‐1 (ET‐1) inhibits NO and contributes to endothelial dysfunction in penile arteries in a model of insulin resistance‐associated erectile dysfunction (ED). Experimental Approach Vascular function was assessed in penile arteries, from obese (OZR) and lean (LZR) Zucker rats, mounted in microvascular myographs. Changes in basal and stimulated levels of superoxide (O2−) were detected by lucigenin‐enhanced chemiluminescence and ET receptor expression was determined by immunohistochemistry. Key Results ET‐1 stimulated acute O2− production that was blunted by tempol and the NADPH oxidase inhibitor, apocynin, but markedly enhanced in obese animals. ET‐1 inhibited the vasorelaxant effects of ACh and of the NO donor S‐nitroso‐N‐acetyl‐DL‐penicillamine in arteries from both LZR and OZR. Selective ETA (BQ123) or ETB receptor (BQ788) antagonists reduced both basal and ET‐1‐stimulated superoxide generation and reversed ET‐1‐induced inhibition of NO‐mediated relaxations in OZR, while only BQ‐123 antagonized ET‐1 actions in LZR. ET‐1‐induced vasoconstriction was markedly enhanced by NO synthase blockade and reduced by endothelium removal and apocynin. In endothelium‐denuded penile arteries, apocynin blunted augmented ET‐1‐induced contractions in OZR. Both ETA and ETB receptors were expressed in smooth muscle and the endothelial layer and up‐regulated in arteries from OZR. Conclusions and Implications ET‐1 stimulates ETA‐mediated NADPH oxidase‐dependent ROS generation, which inhibits endothelial NO bioavailability and contributes to ET‐1‐induced contraction in healthy penile arteries. Enhanced vascular expression of ETB receptors contributes to augmented ROS production, endothelial dysfunction and increased vasoconstriction in erectile tissue from insulin‐resistant obese rats. Hence, antagonism of ETB receptors might improve the ED associated with insulin‐resistant states.